Driving and visual deficits in stroke patients - Braga,Marina Marcondes (2018)
ABSTRACT Objective: The aim of the present study was to conduct an exploratory assessment of visual impairment following stroke, and to discuss the possibilities of reintroducing patients to the activity of driving. Methods: The Useful Field of View test was used to assess visual processing and visual attention. Results: A total of 18 patients were included in the study, and were assigned to either the drive group (n = 9) or the intention group (n = 9). In the drive group, one patient was categorized as moderate-to-high risk; whereas, in the intention group, one patient was categorized as low-to-moderate risk. Additionally, two patients in the intention group were categorized as high risk. The patients did not perceive their visual deficits as a limitation. Conclusion: Visual attention is an interference factor in terms of the safe performance of driving after a stroke. All patients showed a high level of interest for the independence provided through being able to drive.